Korea Its culture and tradition - Korea Press Center (Seoul, South Korea : Korea Press Center, 1992)
The purpose of this slide program is to provide educators and students in the field of Korean studies as well as those with a general interest in Korea with a comprehensive approach to Korea's rich cultural legacy
H-71022
Keywords: Korea (South) -- Social life and customs; Korea -- Civilization; Korea -- History